2021
DOI: 10.1038/s41598-021-84822-5
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory pattern of glycemic control in patients with diabetes mellitus

Abstract: Daily glucose variability is higher in diabetic mellitus (DM) patients which has been related to the severity of the disease. However, it is unclear whether glycemic variability displays a specific pattern oscillation or if it is completely random. Thus, to determine glycemic variability pattern, we measured and analyzed continuous glucose monitoring (CGM) data, in control subjects and patients with DM type-1 (T1D). CGM data was assessed for 6 days (day: 08:00–20:00-h; and night: 20:00–08:00-h). Participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
1
11
4
Order By: Relevance
“…Diabetic patients exhibit oscillatory levels in glucose with daily episodes of hypo- and hyperglycemia, which is thought to be important for driving DM-associated pathologies ( Vasquez-Muñoz et al., 2021 ). Indeed, the term “metabolic memory” coins the pathogenic alterations induced by hyperglycemia long after accomplishment of glycemic control ( Genuth et al., 2002 ; Writing Team for the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Research Group, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diabetic patients exhibit oscillatory levels in glucose with daily episodes of hypo- and hyperglycemia, which is thought to be important for driving DM-associated pathologies ( Vasquez-Muñoz et al., 2021 ). Indeed, the term “metabolic memory” coins the pathogenic alterations induced by hyperglycemia long after accomplishment of glycemic control ( Genuth et al., 2002 ; Writing Team for the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Research Group, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of reference, a lot of previous clinical studies indicated large age ranges in patients and healthy controls. Several clinical studies, for example, showed that 34.68 ± 15.43 years old in 65 patients with diabetes mellitus and 47.33 ± 19.58 years old in 27 healthy controls (94), and that 70.5 ± 2.1 years old in 50 heart failure patients in New York, and 47.9 ± 9.7 years old in 28 healthy university population (95); (d) given the small sample sizes, this study employed two types of measures: first, an endogenous antioxidant system is needed for comparing larger sample size and better-controlled studies described in the Journal of American Medical Association (JAMA) (96). Of reference, the present findings were supported by previous studies (10, 12-15, 97, 98).…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a predictive model to determine maximum and minimum glycemic oscillations and the hour of the day at maximum and minimum glycemic oscillations in patients with T1D [15]; given that patients with T2D display different oscillatory days, we used the same model to test whether it could apply to T2D. Our data indicated that it was possible to predict hyperglycemia (p < 0.001) and hypoglycemia (p < 0.001) in patients with T2D (Fig.…”
Section: The Predictive Model Of Hyperglycemia and Hypoglycemia In Pa...mentioning
confidence: 93%
“…Type 2 DM is characterized by hyperglycemia, increased HbA1c, and overweight [12,13]. Importantly, it has been proposed that the early detection of dysglycemic episodes (acute and chronic glucose excursions) might help improve outcomes in patients with DM [14,15]. Nevertheless, while T2D can be treated with diet, exercise, and medication, there is no accurate classification of glycemic oscillations in patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation